Study of a monoclonal antibody to human B cells - Drover, Mary Sheila Lewis (1986)
Thesis (M.Sc.)--Memorial University of Newfoundland, 1986. Medicine Bibliography: leaves 137-163. The purpose of this work was to characterize and determine the specificity of a mouse monoclonal antibody (NFLD.M1) which was derived from a fusion between SP2/0-Ag14 and spleen cells from a Balb/c mouse that had been hyperimmunized with B-cells from a chronic lymphatic leukemic patient. Cloning was done by limiting dilution and positive clones were selected by screening on a panel of viable cells using the cellular enzyme-linked immunosorbent assay (CELISA). This assay was shown to be more specific and sensitive than an ELISA that used glutaraldehyde-fixed cells. -- Two sources of the antibody (purified IgG1 from ascites fluid and supernatant from overgrown cultures) appeared to be identical in their serological pattern on several B-cell lines. Specificity testing using the CELISA and several different cell types revealed that NFLD.M1 recognized some B-cells, but failed to react with any of the T-cells tested. A Frequency Distribution plot of the data showed that NFLD.M1 reacted with the cells in a bimodal fashion compared to the normal distribution observed with the monomorphic monoclonal antibody, NEI anti-Ia. Furthermore when NFLD.M1 antibody was expressed as a percent of the NEI anti-Ia it was found that all the DR4 positive cells produced values greater than 50% whereas DR4 negative cells gave values less than 30%. Using 30% as a cutoff point a correlation analysis was done on the CELISA results for 42 cell lines. The r value obtained for DR4 and NFLD.M1 was 1 with a p value of 2 x 10-10. In addition significant r values were obtained for DRw53 and DQw3 which are in linkage disequilibrium with DR4. -- 0ne-dimensional electrophoresis of the immunoprecipitated molecules from a DR4 cell produced a banding pattern that was compatible with that of the alpha and beta subunits of DR.